The effect of glycyrrhizic acid on traumatic spinal cord injury in rats - Sehitoglu, M H; Guven, M; Yüksel, Y; Akman, T; Bozkurt Aras, A; Farooqi, A A; Cosar, M (Cellular and Molecular Biology, 2016)
Spine injury associated with traumatic spinal cord injury eventuates in oxidative stress, inflammation and neuronal apoptosis. The aim of this study is to find out whether the glycyrrhizic acid treatment protects spinal cord from traumatic injuries in rats. To this end, the rats were divided into three groups: group I; control group (no drug or operation, n=8), group II; traumatic spinal cord injury group (TSCI, n=8) and group III; glycyrrhizic acid group (TSCI-GA, 80 mg/kg, n=8). Total laminectomy was performed at T10 level. A balloon angioplasty catheter was inserted into the T9 level thoracic spinal cord extradurally. The rats were evaluated with the Tarlov Scale. After 24 hours, spinal cord tissues were taken for biochemical and histopathological examinations. TSCI effectuates unwanted results on tissues, antioxidant systems and cell membranes. Antioxidant enzyme level decreased and lipid peroxidation increased. However, TSCI led to inflammation and apoptosis. Glycyrrhizic acid treatment provided a significant decrease in lipid peroxidation in group III in comparison with group II. Moreover, nuclear respiratory factor 1 levels and superoxide dismutase activity of group III were significantly higher than group II (p<0.05). The histopathological and immunohistochemical results revealed that the numbers of apoptotic and necrotic neuron, edema, hemorrhage, inflammatory cells, NF-ÎºB and S100B expressions were significantly lower than group II (p<0.05). Our study showed that the glycyrrhizic acid treatment reduced oxidative stress and inflammation, and promoted the neuronal functions in traumatic spinal cord injury.